2008
DOI: 10.1128/jvi.01575-08
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus ICP0 Promotes both Histone Removal and Acetylation on Viral DNA during Lytic Infection

Abstract: During lytic infection, the genome of herpes simplex virus 1 (HSV-1) is associated with limited levels of histones but does not form a regular repeating nucleosomal structure. However, the previous observation that chromatin remodeling factors are recruited into viral replication compartments indicates that chromatin remodeling plays a role in HSV-1 gene expression and DNA replication. In this study we demonstrate the presence of histone H3 on HSV-1 DNA early in infection at levels equivalent to those found on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
240
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(265 citation statements)
references
References 84 publications
18
240
0
1
Order By: Relevance
“…First, the entire naked DNA genome is exposed immediately after the invasion (35)(36)(37). Second, although the viral genome packages into chromatin with the host histones, it is less dense and much more loosely packed than the nuclear self-DNA (35)(36)(37). Importantly, we find that the relative binding affinity of IFI16 to various dsDNA fragments changes cooperatively not only with increasing IFI16 concentrations ( Fig.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…First, the entire naked DNA genome is exposed immediately after the invasion (35)(36)(37). Second, although the viral genome packages into chromatin with the host histones, it is less dense and much more loosely packed than the nuclear self-DNA (35)(36)(37). Importantly, we find that the relative binding affinity of IFI16 to various dsDNA fragments changes cooperatively not only with increasing IFI16 concentrations ( Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Although the total amount of viral DNA would never exceed that of self-DNA, there are two features of foreign DNA that are much more conducive to filament formation by IFI16. First, the entire naked DNA genome is exposed immediately after the invasion (35)(36)(37). Second, although the viral genome packages into chromatin with the host histones, it is less dense and much more loosely packed than the nuclear self-DNA (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Histones are rapidly deposited, likely via a cellular response to infection. Whereas the chromatin structure does not appear to be that of canonically spaced nucleosomes, the levels of genomeassociated nucleosomes are similar to that observed on cellular DNA (36). The role of chromatin in regulating HSV-1 gene expression is supported by (i) the presence of nucleosomes exhibiting repressive or activating modifications that correlate with repression or activation of viral gene expression (5,10,11,(36)(37)(38) and (ii) deposition of the histone variant H3.3 on the viral genome and the requirement for the H3.3 histone chaperone HIRA for efficient viral gene expression (39).…”
mentioning
confidence: 69%
“…Although the levels of nucleosomes on the genome appear to be reduced relative to cellular DNA at later times in infection (36,40), the absolute amount of viral DNA associated with histones increases during replication (36). Additionally, it has also been observed that histone H3.1 is incorporated in a replication dependent manner (39), indicating that some level of histone assembly occurs on replicated viral DNA.…”
mentioning
confidence: 96%
“…Because ICP0 does not bind DNA, its most likely function is to recruit to the ND10 bodies at which the DNA is aggregated host proteins that derepress and enable expression of the genes encoded by the DNAs (17,18). Second, ICP0 does not discriminate between viral and irrelevant DNA deposited at the ND10 nuclear bodies.…”
Section: Dna Binding Proteins | Gene Derepressionmentioning
confidence: 99%